Description of Elementary School Children in Choosing Snacks at School - Rukmasari, Ema Arum; Mamuroh, Lilis; Ramdhanie, Gusgus Ghraha; Ama, Yolanda (GoAcademica Research & Publishing, 2024)
School is one of the places where children are active with their peers. Peers and the diversity of education at school are factors that influence children's habits in choosing education in school. Nutritional food can play both a positive and a negative role. Children can identify a variety of foods through the intestine so that they can form an appetite, but when the intestine contains intestines, it can cause disease. The study aims to figure out how school-age children choose to attend school. This research uses cross-sectional methods with a quantitative-descriptive approach. The research instrument used was a modified Safriana consumption questionnaire. stratified random sampling technique, with 270 respondents from class I to class VI. The results showed that boys were more likely to choose unhealthy choices than girls. Class I students were the most likely to make unsafe choices, while class VI students were the most likely to make healthy choices. Most kids choose important foods that are delicious and cheap, and the most popular kind of food is one-piece. It is suggested that the school should have a school canteen that provides healthy food and provides health education to children about the importance of choosing healthy meals.